2013
DOI: 10.4187/respcare.02665
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Volume-Oriented Versus Flow-Oriented Incentive Spirometry on Chest Wall Volumes, Inspiratory Muscle Activity, and Thoracoabdominal Synchrony in the Elderly

Abstract: BACKGROUND: Aging causes physiological and functional changes that impair pulmonary function. Incentive spirometry is widely used for lung expansion, but the effects of volume-oriented incentive spirometry (VIS) versus flow-oriented incentive spirometry (FIS) on chest wall volumes, inspiratory muscle activity, and thoracoabdominal synchrony in the elderly are poorly understood. We compared VIS and FIS in elderly subjects and healthy adult subjects. METHODS: Sixteen elderly subjects (9 women, mean ؎ SD age 70.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 26 publications
0
34
0
1
Order By: Relevance
“…Three articles were found that included information about spirometers. 10,12,22 In these articles, respiratory muscle training, performed using threshold pressure load in inspiratory muscles, was included. 23 A meta-analysis of the data from the randomized clinical trials was included in this review and is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three articles were found that included information about spirometers. 10,12,22 In these articles, respiratory muscle training, performed using threshold pressure load in inspiratory muscles, was included. 23 A meta-analysis of the data from the randomized clinical trials was included in this review and is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…22 There are 2 types of spirometers: volume and flow. 12 The incentive volume spirometer provides an increase in thoracic expansion and reduces asymmetries of these expansions.…”
Section: Practical Implications Of the Incentive Spirometer For Ventimentioning
confidence: 99%
“…Another study 37 compared the effects of incentive spirometry flow (RESPIRON®) and volume (Voldyne®) on lung volumes, thoracoabdominal mobility and inspiratory muscle activity in the elderly people and in healthy adults, evaluated by plethysmography and electromyography, concluding that both the spirometers have similar effects in lung volumes and thoracoabdominal mobility, however, the spirometer flow requires greater respiratory muscle activity. A current study 38 with 48 healthy elderly subjects randomized into group therapy with RESPIRON® and the other therapy group with Voldyne® presented an increase in some variables, such as: respiratory muscle strength, lung function (spirometry values) and thoracoabdominal mobility in both groups by approving these devices as good allies of respiratory therapy.…”
Section: Respiratory Physiotherapy With Elderly Peoplementioning
confidence: 99%
“…Among these, we can highlight the Respiron® IS, which emphasizes the deep inspiration up to total lung capacity, providing visual feedback 7,8 . This type of IS facilitates deep breathing, stimulates high inspired volumes and prevents lung hypoventilation 6,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…The exercises with IS are a simple and safe way to perform breathing training, aiming at the improvement of lung volumes and at the prevention of respiratory complications in children, adults and elderly people 7 .…”
Section: Introductionmentioning
confidence: 99%